Clinical characteristics and outcomes of hospital-manifested COVID-19 among Brazilians - Delfino-Pereira, Polianna; Pires, Magda Carvalho; Gomes, Virginia Mara Reis; Nogueira, Matheus Carvalho Alves; Lima, Maria Clara Pontello Barbosa; Schwarzbold, Alexandre Vargas; Maurílio, Amanda de Oliveira; Scotton, Ana Luiza Bahia Alves; Costa, André Soares de Moura; Farace, Barbara Lopes; de Castro, Bruno Mateus; Cimini, Christiane Corrêa Rodrigues; et al. (Elsevier, 2023)
Objectives: To analyze the clinical characteristics and outcomes of admitted patients with the hospital- versus community-manifested COVID-19 and to evaluate the risk factors related to mortality in the first population. Methods: This retrospective cohort included consecutive adult patients with COVID-19, hospitalized between March and September 2020. The demographic data, clinical characteristics, and outcomes were extracted from medical records. Patients with hospital-manifested COVID-19 (study group) and those with community-manifested COVID-19 (control group) were matched by the propensity score model. Logistic regression models were used to verify the risk factors for mortality in the study group. Results: Among 7,710 hospitalized patients who had COVID-19, 7.2% developed symptoms while admitted for other reasons. Patients with hospital-manifested COVID-19 had a higher prevalence of cancer (19.2% vs 10.8%) and alcoholism (8.8% vs 2.8%) than patients with community-manifested COVID-19 and also had a higher rate of intensive care unit requirement (45.1% vs 35.2%), sepsis (23.8% vs 14.5%), and death (35.8% vs 22.5%) (P <0.05 for all). The factors independently associated with increased mortality in the study group were increasing age, male sex, number of comorbidities, and cancer. Conclusion: Hospital-manifested COVID-19 was associated with increased mortality. Increasing age, male sex, number of comorbidities, and cancer were independent predictors of mortality among those with hospital-manifested COVID-19 disease.
Keywords: Clinical characteristics; COVID-19; Hospital-manifested infection; In-hospital mortality; Outcomes; Risk factors